What Drives Generation Z to Use Pay Later Services in Central Java: Psychological or Demographic Factors? - Partikasari, Retno; Islam, Ayya Agmulia Asmarani; Cahyadin, Malik (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
By identifying through personal usage and/or business usage of BNPL (Buy Now Pay Later) services among generation Z in Central Java, this study examines whether the decision influenced by psychological or demographic factors. This research conducted cross-sectional data collected through questionnaires and implemented multiple regression test such as: multicollinearity test, heteroscedasticity test, normality test, reset test, and MWD (MacKinnon-White-Davidson) in order to determine the most proper functional specifications. It is concluded that variable motivation has a positive and somewhat significant effect on why generation Z in Central Java uses Pay Later services. On the other side, variable easiness has a significant negative effect. Variable age in business use term is the only important factor. Conversely, other variables like income, expense, education does not have a significant effect. The MWD test shows that both linear and log-linear models are equally valid. Offers practical guidance for policy makers, focuses on FinTech (Financial Technology) in fostering more responsible Pay Later utilization to avoid credit risk/default.